2001
DOI: 10.1107/s0907444901006291
|View full text |Cite
|
Sign up to set email alerts
|

Structure of ribosomal protein TL5 complexed with RNA provides new insights into the CTC family of stress proteins

Abstract: The crystal structure of Thermus thermophilus ribosomal protein TL5 in complex with a fragment of Escherichia coli 5S rRNA has been determined at 2.3 A resolution. The protein consists of two domains. The structure of the N-terminal domain is close to the structure of E. coli ribosomal protein L25, but the C-terminal domain represents a new fold composed of seven beta-strands connected by long loops. TL5 binds to the RNA through its N-terminal domain, whereas the C-terminal domain is not included in this inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…The three CTC domains are shown. Domain-1 (red) resembles protein L25; 67 domain-2 (green), which together with domain 1 forms a structure almost identical to that of protein TL5, 68 and domain-3 (gold), which is unique to D. radiodurans. 7 Highlighted are the approximate locations of the B1a intersubunit bridge (also known as the 'A-site finger' or helix H38) and of the acceptor stem of the A-site tRNA (in violet and blue, respectively).…”
Section: Spectacular Ribosomal Architecture Global Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three CTC domains are shown. Domain-1 (red) resembles protein L25; 67 domain-2 (green), which together with domain 1 forms a structure almost identical to that of protein TL5, 68 and domain-3 (gold), which is unique to D. radiodurans. 7 Highlighted are the approximate locations of the B1a intersubunit bridge (also known as the 'A-site finger' or helix H38) and of the acceptor stem of the A-site tRNA (in violet and blue, respectively).…”
Section: Spectacular Ribosomal Architecture Global Motionsmentioning
confidence: 99%
“…2 The fold of a hypothetical D50S protein, built from the CTC N-terminal and middle domains is almost identical to the fold of the two-domain protein TL5 from T. thermophilus. 68 The slight changes in the relative orientations of the two domains in the two proteins can be correlated with crystal vs ribosome environments. Hence, it seems that TL5 occupies the same position, namely wraps around a B1a bridge, in the T. thermophilus ribosome.…”
Section: Tunnel Discrimination Of Nascent Proteinsmentioning
confidence: 99%
“…The C-terminal domain (also known as domain 1) is homologous to protein L25 in E. coli, namely the 5S rRNA-binding protein. Domains 1 + 2 (namely the C-terminal + the middle domains) are homologous to protein TL5 in the T. thermophilus ribosome (124). Domain 3 (the N-terminal domain) is bound to the middle domain (domain 2) by a single strand, presumably facilitating the extreme (unusual) flexibility in its position within the ribosome, as indicated by the lower quality of its electron density map.…”
Section: Ctc a Multidomain Protein Containing A Domain Typical To Mamentioning
confidence: 99%
“…The structures of two of the four YbbR domain--containing proteins from Desulfitobacterium hafniense Y51 have been solved by NMR and X--ray crystallography 26 . It was noted that the YbbR domains assume a similar fold to the C--terminal domain of the ribosomal proteins TL5 from Thermus thermophilus and L25 from Deinococcus radiodurans 27,28 . It has been suggested that this domain serves to stabilize the interaction between the 5S rRNA, to which these proteins bind, and the 23S rRNA via an interaction with the 23S rRNA--binding ribosomal protein L16 26 , highlighting that a protein with a similar fold to YbbR can bind both RNA and proteins.…”
Section: Synthesis Of C--di--ampmentioning
confidence: 99%